Scenario driven requirement engineering for design and deployment of mobile communication networks - Jan Markendahl; Bengt G. Mölleryd; Claes Beckman; Östen Mäkitalo (International Telecommunications Society (ITS), 2011)
The numbers of users and usage of mobile data service are increasing dramatically due to the introduction of smartphones and mobile broadband dongles. For the next decade the mobile broadband market is expected to grow and reach a level where the average data consumption per user is orders of magnitude greater than today. For the telecom industry it is a magnificent challenge to design and deploy these s high-capacity wireless networks taking into account limitations in cost, energy and radio spectrum. The objective of this paper is to highlight the need to consider a multitude of scenarios for the requirements, design and deployment of mobile broad band networks. The R&D has for many years been targeting high peak data rates enabled by improved spectral efficiency, adding more spectrum bands, aggregation of frequency bands and offloading to local wireless networks connected via public fixed phones or broadband. However, many of these features driving the technology development are representative for the conditions in US and Western Europe. The wireless networks also need to be designed assuming deployment in regions in the world where both the availability of spectrum as well as the penetration of fixed phones and broadband are limited.
Keywords: L96; O32; O13; 330; Mobile broadband networks; cost and capacity; spectrum; deployment strategies; telecommunications; management of technology and R&D; economic development of natural resources